2021
DOI: 10.3390/pathogens10050602
|View full text |Cite
|
Sign up to set email alerts
|

Do All Roads Lead to Rome? The Potential of Different Approaches to Diagnose Aelurostrongylus abstrusus Infection in Cats

Abstract: An infection with the cat lungworm, Aelurostrongylus abstrusus, can be subclinical, but it can also cause severe respiratory clinical signs. Larvae excretion, antibody levels, clinical assessment findings of the respiratory system and diagnostic imaging findings were recorded and compared for six cats with experimental aelurostrongylosis. In five cats, patency started 33–47 days post infection (pi), but two cats excreted larvae only in long intervals and low numbers. Positive ELISA results were observed in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…Overall, these results are comparable to data from Switzerland, a country bordering the south of Germany: 10.7% of 4067 cats were seropositive for A. abstrusus antibodies [ 18 ], whereas between 0.8% and 2.3% of cats were coproscopically positive, with a higher prevalence in stray cats (6.5%) than owned cats (0.7%) [ 1 , 31 ]. Experimental studies showed that antibodies were detectable already 2–3 weeks before the onset of larval excretion [ 19 ], although isolated individuals may seroconvert later than 10 weeks post-infection [ 32 ]. Antibodies were then shown to persist as long as worms were present, therefore not necessarily correlating with patency [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, these results are comparable to data from Switzerland, a country bordering the south of Germany: 10.7% of 4067 cats were seropositive for A. abstrusus antibodies [ 18 ], whereas between 0.8% and 2.3% of cats were coproscopically positive, with a higher prevalence in stray cats (6.5%) than owned cats (0.7%) [ 1 , 31 ]. Experimental studies showed that antibodies were detectable already 2–3 weeks before the onset of larval excretion [ 19 ], although isolated individuals may seroconvert later than 10 weeks post-infection [ 32 ]. Antibodies were then shown to persist as long as worms were present, therefore not necessarily correlating with patency [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies were then shown to persist as long as worms were present, therefore not necessarily correlating with patency [ 19 ]. Overall, a correlation between optical density (OD) values and the number of L1 per gram of faeces was observed, and it was concluded that low larval excretion may lead to OD values below the test threshold [ 32 ]. Antibodies also persisted for weeks after anthelmintic treatment [ 19 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it allows diagnosis only during the patency period, and the sensitivity is impaired by intermittent and/or low excretion of larvae. Molecular detection by PCR from feces or pharyngeal swabs can be used as alternative diagnostic tools for feline aelurostrongylosis [24][25][26]. An ELISA test for detection of A. abstrusus antibodies in serum has been used to improve the diagnosis of feline aelurostrongylosis [24,27].…”
Section: Introductionmentioning
confidence: 99%